SINERGI KOMISI PENYIARAN INDONESIA (KPI) DAERAH KALIMANTAN TENGAH BERSAMA BALAI BESAR PENGAWAS OBAT DAN MAKANAN (BBPOM) PALANGKA RAYA (Studi Kasus Pelanggaran Etika Iklan Obat Tradisional) - Nupus Nupus; Desi Erawati; Nurliana Nurliana; Nisa Rahimia (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2023)
Traditional medicine advertisements have become a familiar aspect of society. However, in some instances, misleading or inaccurate advertisements can raise concerns regarding safety and effectiveness. A synergistic approach between the Central Kalimantan Regional Indonesian Broadcasting Commission and the Palangka Raya Central Drug and Food Control Agency (BPOM) is necessary to address violations of traditional medicine advertisements, particularly in Central Kalimantan. In the literature review, various studies highlighted violations of traditional medicine advertisements and their impact on society and public health. This paper aims to measure the extent of synergism between these two entities in addressing advertisement violations and propose possible solutions. The research methodology involves qualitative analysis through a case study approach, where the Central Kalimantan Regional Indonesian Broadcasting Commission serves as the primary data source for violations of traditional medicine advertisements, identified through monitoring processes, supported by a literature review from the Palangka Raya Central BPOM. Data is collected through surveys, interviews with relevant parties, and analysis of regulations-related documents. The research results reveal a gap between identified violations of traditional medicine advertisements and the actions taken by both relevant entities. This indicates the need for simultaneous synergy between the Central Kalimantan Regional Indonesian Broadcasting Commission and the Palangka Raya Central BPOM in addressing these violations. The discussion highlights the importance of enhancing cooperation among authorities, relevant agencies, and the public to support compliance with advertisement regulations.